PENERAPANTOTALQUALITYMANAGEMENT(TQM)DAN PENGARUHNYATERHADAP KINERJAKARYAWAN (StudiKasus:PT.Daya Cipta Kemasindo, Tangerang) - Wiratmo, Bambang (Reaktom : Rekayasa Keteknikan dan Optimasi, 2016)
ThepurposeofthisresearchistoinvestigatetheeffectofTQMpracticesimplementationwhichconsistsofleadership,strategicplanning,customerfocus,informationandanalysis,peoplemanagement,andprocessmanagementonemployeeperformanceatPT.Daya Cipta Kemasindo Tangerang.Thepopulationwere400employeesand270employeesasrespondent.Thesampleobtainedbasedonsimplerandomsamplingmethod.BothdescriptivestatisticandStructuralEquationModelling(SEM)were employedtotesttheeffectamong variables. Dataprocessing were usedbySPSSandAMOS 16.00.Thefindingofresearchindicatesthat:TQMpracticesimplementationwhichconsistsofleadership,strategicplanning,customerfocus,informationandanalysis,peoplemanagement,andprocessmanagementhavesignificantlyandpositiveeffectonemployeeperformance.Keywords:ImplementationofTQMpractices,employeeperformance.